ANALYSIS OF THE ROLE OF CROWN WITNESSES IN CRIMINAL TRIALS - kurniawan, itok (PT. Media Akademik Publisher, 2024)
Witnesses are quite important pieces of evidence in a criminal case examination. This is because a description of criminal events in the past can be revealed by a witness. In the event of a shortage of witnesses, in a crime committed by more than 1 (one) person, witnesses can be obtained from other defendants. Witnesses who are defendants in separate case files are referred to as crown witnesses. This article aims to determine the role and contribution of crown witnesses in criminal case examinations. The writing method used is normative legal research with a statutory approach. The results of this research are that the existence of crown witnesses and their role in evidence varies in each case or is casuistic. Crown witnesses are ideally used when there is a shortage of witnesses or the principle of unus testis nullus testis is not fulfilled.